LEGAL REVIEW OF PERSONAL DATA PROTECTION FOR CHILDREN IN THE DIGITAL SPACE AND THE RESPONSIBILITY OF SOCIAL MEDIA PLATFORMS - Nopit Ernasari; Fariz Rifqi Hasbi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The proliferation of social media and digital platforms has increased the risk of misuse of children's personal data in the digital space, making children vulnerable to cybercrimes such as cyberbullying and identity theft due to a lack of understanding of privacy. This legal review analyzes the international (UDHR Article 12 and CRC 1989) and national (1945 Constitution, Child Protection Law, ITE Law, and 2022 PDP Law) legal frameworks for protecting children's specific personal data. The study shows that although the PDP Law classifies children's data as specific and requires parental consent, its implementation is still hampered by a lack of derivative regulations and low digital literacy. Social media platforms, as PSEs, have preventive and curative responsibilities, reinforced by the 2025 TUNAS Government Regulation, which mandates content filtering and rapid reporting. This study recommends the issuance of derivative regulations, digital education, and multistakeholder collaboration to create a child-safe digital ecosystem.